The mother : a novel - Edwards, Yvvette (New York : Amistad, an imprint of HarperCollins Publishers, 2016)
"... in a single moment Marcia is stripped clean of everything she had presumed was her for keeps. Ryan, not the kind of boy to find himself on the wrong end of a knife, is brutally murdered. Consumed by grief and rage...she must go to court alone for the trial of her son's killer, Tyson, another teenage boy. As the trial takes apart her son's life and reassembles it in front of strangers, Marcia, always certain of Ryan's virtues, finds her beliefs and assumptions challenged as she learns more about her son's death and of Tyson's life" --inside front cover.
Keywords: Mothers -- Fiction; Motherhood -- Fiction; Murder -- Fiction; Grief -- Fiction